2014
DOI: 10.1177/000313481408000725
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Interhospital Transfers on Surgical Quality Metrics for Academic Medical Centers

Abstract: The emergence of pay-for-performance systems pose a risk to an academic medical center's (AMC) mission to provide care for interhospital surgical transfer patients. This study examines quality metrics and resource consumption for a sample of these patients from the University Health System Consortium (UHC) and our Department of Surgery (DOS). Standard benchmarks, including mortality rate, length of stay (LOS), and cost, were used to evaluate the impact of inter-hospital surgical transfers versus direct admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…A 2014 US study of surgical quality metrics for academic medical centres found that interhospital transfer was associated with higher mortality rate, longer length of stay and higher consumption of resources including intensive care (53 versus 32% for direct admissions), respiratory therapy (53 versus 42%), imaging (92 versus 82%) and rehabilitation services (63 versus 49%) . Mean total costs were over 50% higher for transferred patients compared with direct admissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2014 US study of surgical quality metrics for academic medical centres found that interhospital transfer was associated with higher mortality rate, longer length of stay and higher consumption of resources including intensive care (53 versus 32% for direct admissions), respiratory therapy (53 versus 42%), imaging (92 versus 82%) and rehabilitation services (63 versus 49%) . Mean total costs were over 50% higher for transferred patients compared with direct admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Mean total costs were over 50% higher for transferred patients compared with direct admissions. Mean intensive care unit (ICU) stay was 2.5 days longer and mean ICU costs were $17 823 and $11 887, respectively …”
Section: Discussionmentioning
confidence: 99%
“…Currently, national improvement measures do not account for this, and studies have shown that this penalizes hospitals accepting transfers. 7,9,12…”
Section: Discussionmentioning
confidence: 99%
“…However, securing these services often requires travelling burdensome distances away from patients’ homes and communities of support. Furthermore, these patients often arrive with poorly defined goals of care and experience unfavorable outcomes including higher rates of mortality [ 3 6 ]. The challenge is compounded by the fact that the transferred patients and families frequently do not understand the severity of illness, leading to unrealistic expectations and a potentially false sense of hope [ 7 ].…”
Section: Introductionmentioning
confidence: 99%